2013
DOI: 10.7567/apex.6.127101
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Acoustic Energy Harvesting Using Coupled Resonance Structure of Sonic Crystal and Helmholtz Resonator

Abstract: An acoustic energy harvester using a coupled resonance structure of a sonic crystal resonator and an electromechanical Helmholtz resonator with a piezoelectric composite diaphragm is proposed to enhance energy harvesting. Due to acoustic resonance coupling between the sonic crystal resonator and the Helmholtz resonator, the coupled resonance structure has a larger acoustic pressure magnification than each individual resonator structure. Consequently, the stronger vibration of the diaphragm and the higher harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 22 publications
0
42
0
Order By: Relevance
“…Only a few research groups have studied this area with a focus on polarization-patterned piezoelectric solids [17], quarter-wavelength resonators [18], Helmholtz resonators [19][20] and phononic crystals [21][22][23][24]. In addition, Yang et al [25] combined the sonic crystal concept with the Helmholtz resonators to enhance the acoustic energy harvesting. Furthermore, as shown recently, acoustic metamaterials can be used to enhance energy harvesting by changing wave propagation.…”
Section: Introductionmentioning
confidence: 98%
“…Only a few research groups have studied this area with a focus on polarization-patterned piezoelectric solids [17], quarter-wavelength resonators [18], Helmholtz resonators [19][20] and phononic crystals [21][22][23][24]. In addition, Yang et al [25] combined the sonic crystal concept with the Helmholtz resonators to enhance the acoustic energy harvesting. Furthermore, as shown recently, acoustic metamaterials can be used to enhance energy harvesting by changing wave propagation.…”
Section: Introductionmentioning
confidence: 98%
“…The amplified cavity pressure drives the vibration of the piezoelectric plate mounted on the back plate or in the cavity of Helmholtz resonator, the electric energy is thus induced by the piezoelectric effect. On the other hand, the sonic crystal configuration has also been exploited in acoustic energy harvesting [16][17][18]. Owing to the acoustic wave localization effect inside the sonic crystal cavity, the cavity pressure is greatly magnified to deform the piezoelectric material.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic energy is another potential source for power generation. The increasing research studies about acoustic energy harvesting have been reported [12][13][14][15][16][17][18]. The Helmholtz resonator is widely used in the acoustic energy harvester systems since it can largely amplify the acoustic pressure in its cavity [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Vibration-based energy harvester using piezoelectric material is widely adopted owing to its high energy density, simple structure and easy miniaturization. [1][2][3][4][5] Conventional linear piezoelectric energy harvesting devices only work optimally near their resonance frequencies with a narrow frequency bandwidth around a particular resonant frequency. 6 However, vibration existing in environments generally has a wide band of frequency.…”
Section: Introductionmentioning
confidence: 99%